Perfil dos professores que atuam na EJA no município de Humaitá-AM: um olhar sobre a formação - Beleza, Janderlane Oliveira (Brasil, 2019)
This is a final project, starting from a research of scientific initiation, entitled "Profile of teachers working in the EJA in the city of Humaitá-AM: A look at the formation". Our objective is to draw the profile of teachers who work in urban municipal schools in the form of EJA, and relate to the initial and continuing education of these teachers Youth and Adult Education, addressing the historical context in Brazil and the state of Amazonas, to understand how this type of teaching was conceived throughout the history of Brazil. The developed work has as theoretical foundation the following authors: Freire (1997), Carvalho (2009), Haddad and Di Pierro (2000), Romão (2007), Miranda (2012) among others, whose studies transmit a primordial education for the understanding of the human condition in society. The discussions about the formation of teachers who work in the EJA modality are diverse, mainly because they have the responsibility to keep the students in class. For data analysis we opted for a quantitative and qualitative research because, there was no strict distinction between quantitative or qualitative research that thus provided the best strategy to understand the researched phenomena and, we conducted bibliographic study and field research, data collection was performed through questionnaire and interview.